3 generations [videorecording (DVD)] - Dellal, Gaby; Watts, Naomi, 1968-; Fanning, Elle, 1998-; Sarandon, Susan, 1946-; Donovan, Tate (Anchor Bay Entertainment, 2017)
After Ray decides to transition from female to male, Ray's mother, Maggie, must come to terms with the decision while tracking down Ray's biological father to get his legal consent.